Testing creation cold dark matter cosmology with the radiation temperature–redshift relation - Baranov, Iuri P. R.; Jesus, José F. [UNESP]; Lima, José A. S. (Springer Nature, 2019)
The standard ΛCDM model can be mimicked at the background and perturbative levels (linear and non-linear) by a class of gravitationally induced particle production cosmology dubbed CCDM cosmology. However, the radiation component in the CCDM model follows a slightly different temperature–redshift T(z)-law which depends on an extra parameter, ν r , describing the subdominant photon production rate. Here we perform a statistical analysis based on a compilation of 36 recent measurements of T(z) at low and intermediate redshifts. The likelihood of the production rate in CCDM cosmologies is constrained by νr=0.024-0.024+0.026 (1 σ confidence level), thereby showing that ΛCDM (ν r = 0) is still compatible with the adopted data sample. Although being hardly differentiated in the dynamic sector (cosmic history and matter fluctuations), the so-called thermal sector (temperature law, abundances of thermal relics and CMB power spectrum) offers a clear possibility for crucial tests confronting ΛCDM and CCDM cosmologies.
Keywords: Cosmic microwave background radiation; Cosmology; Creation of matter and radiation